SPEECH-CONTROLLED MULTI-DISPENSER SYSTEM (International Journal of Food and Nutritional Sciences, 2021)
The speech-based multi dispenser system is an innovative project that integrates speech recognition, artificial intelligence (AI), machine learning (ML), and Raspberry Pi to create a smart liquid dispensing solution. The system aims to provide convenient and precise control over the dispensing based on voice commands from the user. The project utilizes a Raspberry Pi as the central control unit, along with a motor driver IC (such as L293D) to control the dispensing mechanism. The system incorporates a microphone to capture voice commands, which are processed using AI and ML algorithms to accurately recognize and interpret the user's instructions. Upon receiving a valid voice command, the system translates it into specific actions for the motor driver IC. The motor driver IC controls the motors responsible for dispensing, enabling accurate and controlled dispensing according to the user's request.Additionally, the project is complemented with a mobile app interface that displays the status of the motors. The advantages of the speech-based multi-liquid dispenser system include ease of use, hands-free operation, precise liquid dispensing, remote control capabilities, and the ability to customize and monitor dispensing settings. The project opens up possibilities for various applications such as automated beverage dispensing, chemical mixing, pharmaceutical preparations, and more. By incorporating AI and ML techniques, the system can continuously improve its voice recognition capabilities and adapt to user preferences over time. The integration of Raspberry Pi and motor driver IC allows for seamless control and automation of the dispensing process.Overall, the speech-based multi dispenser system offers a user-friendly and intelligent solution for precise liquid dispensing, combining the power of voice recognition, AI, ML, and Raspberry Pi to enhance convenience and efficiency in various dispensing applications.